Audiovisual reality for educational quality in universities: Case study - Silva Hernández, Francisca (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
In the transformative and assurance processes in the educational quality of the Universities, it is important to consider aspects that allow the development and increase of the indicators in the educational programs of the Universities. This document describes in particular a case study of a Public University in Mexico, in terms of the insertion and development of actions and strategies of audio visual reality applied to undergraduate and postgraduate educational programs, in dialogue with the academic, research and administrative processes, resulting in a progressive advance that is required.